Analysis and Implementation of Six Sigma in the Design of an Information System at the Bank Indonesia Canteen North Sumatra - Feby Paulina; Yoshida Sary (Tsabit Journal of Computer Science, 2025)
The conventional cafeteria services at the Representative Office of Bank Indonesia in North Sumatra Province encounter various problems, such as long queues, order recording errors, and limited access to menu information, all of which affect customer satisfaction. This study aims to analyze and implement the Six Sigma method in the design of a web-based cafeteria information system to improve service quality. Using the DMAIC (Define, Measure, Analyze, Improve, Control) framework as the core of the Six Sigma approach and the waterfall model for system development, the system was built with features such as online ordering, real-time menu information, and digital payment integration. The evaluation results showed a Defects Per Million Opportunities (DPMO) value of 93,000 and a Sigma Level of 2.82, indicating a moderate improvement in service quality. The system also achieved a customer satisfaction rate of 90.6%, although some aspects such as order waiting time estimation and ease of use still require improvement. Overall, the implementation of Six Sigma has proven effective in analyzing and enhancing the cafeteria service process through an integrated information system, contributing to better operational efficiency and user experience.